A review of Eteone Savigny, 1820, Mysta Malmgren, 1865 and Hypereteone Bergström, 1914 (Polychaeta: Phyllodocidae) - Wilson, Robin S. (Memoirs of the Museum of Victoria, 1988)
Eteone sensu lato is reviewed and three genera recognised: Hypereteone Bergström, 1914 is resurrected and redefined; Mysta Malmgren, 1865 is retained unchanged and Eteone Savigny,1820 is redefined to include all remaining species. Hypereteone now comprises nine nominal species including H. otati and H. tingara which are described as new species. An apparently undescribed species of Hypereteone is also recognised and H. alba (Webster, 1879), H. barantollae (Fauvel, 1932), H. fauchaldi (Kravitz and Jones, 1979), H. foliosa (Quatrefages, 1865), H. heteropoda (Hartman, 1951) and H. lighti (Hartman, 1936) are proposed as new combinations. Mysta now includes seven nominal species and one undescribed form, and M. platycephala (Augener, 1913) is proposed as a new combination. Eteone sensu stricto now includes 28 nominal species of which four are designated nomina dubia. Eteone palari and E. tulua are described as new species. Keys are provided to distinguish the three genera and all well-described species within each genus. Australian species in all three genera are distinguished in a separate key.
World Polychaeta Database (WPolyDb)